Hubungan Persepsi Siswa Dengan Motivasi Belajar Pada Mata Pelajaran Matematika Siswa Kelas IV Di Sekolah Dasar Negeri 163 Pekanbaru - Nainggolan, Rosinda Nainggolan; Alim, Jesi Alexander Alim Alexander; ', Lismasila (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Mathematics education is one of the most important science in and for our lives. But many students have a negative perception towards learning mathematics, resulting in low motivation to learn. This is reinforced by the implications of the theory of hedonism that is the assumption that all people will tend to avoid things that are difficult and troublesome, or that contain heavy risks, and prefer to do things that bring pleasure to him. Therefore, this study aimed to determine the relationship of perception of students with the motivation to learn in mathematics in the fourth grade students of State Elementary School 163 Pekanbaru. The research method used in this research is correlational method. The sample was graders IVC totaling 37 people consisting of 23 male students and 14 female students. The research instrument used in the form of a questionnaire consisting of 29 positive and negative statements using a Likert scale. The results showed that there was a significant relationship between the perception of students with mathematics learning motivation shown by the increase or decrease in the quantity of students' perception in mathematics will be followed linearly by the increase or decrease in the quantity of motivation to learn mathematics. Key Word: Perceptions of Students About Mathematics, Motivation to Learn Mathematics, Correlation.